American council on ECP (ACE): Why now?. Issue 4 (25th March 2018) - Edelson, Richard; Wu, Yanyun; Schneiderman, Jennifer
Abstract : Stimulated by the scientific progress in deciphering the principal elements contributing to the clinical efficacy of extracorporeal photochemotherapy (ECP), the American Council on ECP (ACE) was formed, under the auspices of the American Society for Apheresis (ASFA), to develop a field‐guiding Consensus Report. ACE is composed of thirty nationally recognized ECP experts, clinically spanning cancer, transplantation, and autoimmunity and scientifically bridging immunology, bioengineering, and hematology. The two‐day meeting took place in Manhattan, April 13‐14, 2017, and unanimous consensus on nine pivotal points is herein reported. (1) ECP's clinical evolution must now enter a scientifically driven phase. (2) ECP is currently a bidirectional therapy, both immunizing and tolerizing simultaneously, via a single one‐size‐fits‐all inflexible medical device. (3) To preclude inadvertent tolerization in the cancer setting, or immunization in the transplant rejection setting, polarization of ECP to either immunization or tolerization mode to match the clinical need is now possible and necessary. (4) Cutaneous T cell lymphoma (CTCL) is a genetically driven cancer, whose response to ECP is due to enhanced anti‐cancer immunity. (5) ECP is a dendritic antigen‐presenting cell (DC) based therapy. (6) ECP's efficacy can now be tested in a broad array of cancers. (7) ECP's capacity to tolerize to allotransplants via processing of donor leukocytes merits expedited human investigation. (8) UVA‐8‐MOP‐impacted ECP‐induced DC are potent antigen‐specific tolerizing agents, while UVA‐8‐MOP(8‐Methoxypsoralen)‐spared ECP‐induced DC are potent antigen‐specific immunizing agents. (9) Six pilot clinical trial areas (CTCL, graft‐vs.‐host disease, ovarian carcinoma, anti‐graft cytotoxic antibodies, pemphigus vulgaris, and haplotype mismatched stem cell transplants) are advised. ACE will be an ongoing advisory group for the field, with the goal of overseeing coordinated clinical and fundamental research efforts.